m6A‐Modified circTET2 Interacting with HNRNPC Regulates Fatty Acid Oxidation to Promote the Proliferation of Chronic Lymphocytic Leukemia - Zijuan Wu; Xiaoling Zuo; Wei Zhang; Yongle Li; Renfu Gui; Jiayan Leng; Haorui Shen; Bihui Pan; Lei Fan; Jianyong Li; Hui Jin (Advanced Science, 2023)
Abstract Chronic lymphocytic leukemia (CLL) is a hematological malignancy with high metabolic heterogeneity. N6‐methyladenosine (m6A) modification plays an important role in metabolism through regulating circular RNAs (circRNAs). However, the underlying mechanism is not yet fully understood in CLL. Herein, an m6A scoring system and an m6A‐related circRNA prognostic signature are established, and circTET2 as a potential prognostic biomarker for CLL is identified. The level of m6A modification is found to affect the transport of circTET2 out of the nucleus. By interacting with the RNA‐binding protein (RBP) heterogeneous nuclear ribonucleoprotein C (HNRNPC), circTET2 regulates the stability of CPT1A and participates in the lipid metabolism and proliferation of CLL cells through mTORC1 signaling pathway. The mTOR inhibitor dactolisib and FAO inhibitor perhexiline exert a synergistic effect on CLL cells. In addition, the biogenesis of circTET2 can be affected by the splicing process and the RBPs RBMX and YTHDC1. CP028, a splicing inhibitor, modulates the expression of circTET2 and shows pronounced inhibitory effects. In summary, circTET2 plays an important role in the modulation of lipid metabolism and cell proliferation in CLL. This study demonstrates the clinical value of circTET2 as a prognostic indicator as well as provides novel insights in targeting treatment for CLL.